The efficacy of propylene oxide, ethyl formate, and ethanedinitrile as fumigants to control Lasioderma serricorne (Fabricius, 1792) (Coleoptera: Anobiidae), Tyrophagus putrescentiae (Schrank, 1781) (Sarcoptiformes: Acaridae), and Necrobia rufipes (De Geer, 1775) (Coleoptera: Cleridae) - Maille, Jacqueline Marie (Kansas State University, 2019)
It is estimated that 1/3 of harvested food is lost to stored product pests. Lasioderma serricorne (Fabricius) (Coleoptera: Anobiidae), Tyrophagus putrescentiae (Schrank) (Sarcoptiformes: Acaridae), and Necrobia rufipes (De Geer) (Coleoptera: Cleridae) are harmful pests to several high-valued stored products such as tobacco, dry-cured meats, and pet foods. Due to the phase-out of methyl bromide, the corrosive properties of phosphine, the increasing global populations of L. serricorne that are becoming resistant to phosphine, and the ineffectiveness of sulfuryl fluoride to control L. serricorne, T. putrescentiae or N. rufipes, there is a need for alternative fumigants that are effective at controlling these pests and reducing post-harvest losses. Propylene oxide (PPO), ethyl formate (EF), and ethanedinitrile (EDN) are used as fumigants to control several stored product pests. However, thorough studies to control L. serricorne, T. putrescentiae, and N. rufipes are lacking. Thus, laboratory experiments were conducted with propylene oxide, ethyl formate, or ethanedinitrile to evaluate the efficacy of each fumigant at controlling these pests. PPO fumigation indicated that the most tolerant life stage of L. serricorne was the larval stage, with an estimated LC₅₀ of 41.08 mg/L. The most tolerant stage of L. serricorne was the pupal stage, with an estimated LC₅₀ of 28.14 mg/L when EF was used. T. putrescentiae eggs were the most tolerant life stage with an estimated LC₅₀ of 0.87 mg/L PPO, and an LC₅₀ of 19.74 mg/L EF, respectively. T. putrescentiae eggs were also the most tolerant life stage to EDN fumigation, with an estimated LC₅₀ of 283.37 ppm. Time-response assays indicated complete mortality of L. serricorne larvae within 3 h at a concentration of 70.09 mg/L PPO. L. serricorne pupae were completely controlled within 3 h when 95.22 mg/L EF was used. Total mortality of T. putrescentiae did not occur within 12 h when PPO was used at a concentration of 71.42 mg/L but did occur at 70.09 mg/L EF. L. serricorne mixed life stages were controlled entirely for six weeks after a 24 h exposure of either fumigant at 25 °C ± 1 °C with 70% R.H. in 16:8 (L:D). T. putrescentiae mixed life stage fumigations yielded less than one mobile T. putrescentiae, emerging after 24 h exposure of 186.9 mg/L PPO at 25 °C ± 1 °C with 70% R.H. in 16:8 (L:D). Exposure of PPO at the same application rate provided complete control for N. rufipes and complete control of T. putrescentiae and N. rufipes after a 24 h exposure of 190.4 mg/L EF at the same conditions. Mixed life stage control of T. putrescentiae was achieved at an EDN concentration of 600 ppm, and less than 0.05% of the population survived after a treatment of 300 ppm within a 24 h treatment at 25 °C. The sorption of PPO reduced mortality by 20%, 30%, and 80% in pet food, flour, and tobacco, respectively, for a 12 h exposure. There was a 10%, 30%, and 40% mortality reduction in pet food, flour, and tobacco when exposed to PPO for 24 h. There was no significant impact on mortality during a 12 h EF exposure; however, there was a 10% mortality reduction in tobacco with a 24 h EF exposure. Sorption of 93.5 mg/L PPO increased the survivability of T. putrescentiae mobile stages by less than 0.05% in fishmeal, ham, or pet food for 12 h and 24 h exposures. There was less than an 8% survivability increase for T. putrescentiae larvae and less than a 0.02% increase for T. putrescentiae mobiles in any of the selected commodities when exposed to 95.2 mg/L EF for 24 h or 12 h. Neither gas desorbed significantly enough to impact the survival of T. putrescentiae mobiles, L. serricorne larvae, or L. serricorne pupae in any of the fumigated commodities for either exposure time of 12 h or 24 h. These studies support that alternatives such as PPO, EF, and EDN are effective at controlling L. serricorne, T. putrescentiae, and N. rufipes on select commodities. Future studies using commercially formulated products should be conducted to determine if they are also able to control these pests. Quantitative sorption and desorption assays on selected products of these pests and the addition of residual analyses would be an applicable approach to further support these alternative fumigants in receiving regulatory approval from government agencies as pesticides on commodities in the U.S.
Keywords: Cigarette beetle; Mold mite; Red-legged ham beetle; Tobacco; Dry-cured ham; Pet food